Morphological behaviour, electronic bond formation and electrochemical performance study of V2O5-polyaniline composite and its application in asymmetric supercapacitor. (November 2018) - Roy, Atanu; Ray, Apurba; Sadhukhan, Priyabrata; Saha, Samik; Das, Sachindranath
Graphical abstract: Highlights: Interlinked V2 O5 -PANI composites are synthesized by chemical polymerization. V2 O5 -PANI exhibits the highest capacitance of 529.56 F g −1 with wide window of 1.6 V. Correlation between electrochemical performances with IR peak shifts is studied. Inorganic-organic synergistic effect plays crucial role for wide working window. Asymmetric supercapacitor exhibits high energy and power in wide potential windows. Abstract: To meet the demand of high-energy density supercapacitors, development of suitable electrode material with a wide potential window and high specific capacitance is most important. In this report, we have synthesized V2 O5 -PANI nanocomposite through in-situ intercalation and polymerization reaction of aniline with V2 O5, which shows a wide potential window as well as high specific capacitance. XRD, SEM and FTIR have been used to characterize the electrode materials. Their electrochemical activity and pseudocapacitive performances were investigated. The correlation between morphology and electrochemical performances were investigated which is a vital way for the selection of electrode materials. Due to the organic-inorganic compatibility, V2 O5 -PANI exhibits good electrochemical charge storage in a wide potential window of 1.6 V (ranging between −0.4 V to 1.2 V) with excellent stability of 84.2% capacitance retention after 5000 GCD cycles. Moreover, asymmetric supercapacitor was assembled V2 O5 -PANI composite and NiMn2 O4 electrodes which yield remarkable energy and power density.